The red badge of courage - Ho, Oliver; Akib, Jamel (New York : Sterling Publishing, 2006)
An abridged version of an adventure in seventeenth-century France, when young d'Artagnan initially quarrels with, then befriends, three musketeers and joins them in trying to outwit the enemies of the king and queen.
Keywords: France -- History -- Louis XIII, 1610-1643 -- Juvenile fiction; France -- History -- Louis XIII, 1610-1643 -- Fiction; Adventure fiction; Action and adventure fiction